2021
DOI: 10.1002/jmv.26877
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peripheral blood cytokines in patients with severe fever with thrombocytopenia syndrome

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is recognized as an emerging infectious disease. This study aimed to investigate the pathogenic mechanism of SFTS. A total of 100 subjects were randomly included in the study. Cytokine levels were detected by enzyme‐linked immunosorbent assay and the viral load was detected by micro drop digital PCR. The results showed that levels of interleukin‐6 (IL‐6), IL‐8, IL‐10, IFN‐inducible protein‐10 (IP‐10), monocyte chemoattractant protein‐1 (MCP‐1), macrophage infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
3
21
1
Order By: Relevance
“…In the trend of cytokine changes, TNF-α, IL-2R and IL-1B reached the peak at 4-6 days after admission, while IL-6 and IL-8 increased slowly. Interestingly, IL-10 tended to decline after admission until it nally returned to the normal reference range, which is quite different from He et al (29). We speculated that this might be because the 15 patients with dynamic cytokine changes collected in this study were treated with cyclic gamma-globulin combined with ribavirin immediately after admission.…”
Section: Discussioncontrasting
confidence: 72%
“…In the trend of cytokine changes, TNF-α, IL-2R and IL-1B reached the peak at 4-6 days after admission, while IL-6 and IL-8 increased slowly. Interestingly, IL-10 tended to decline after admission until it nally returned to the normal reference range, which is quite different from He et al (29). We speculated that this might be because the 15 patients with dynamic cytokine changes collected in this study were treated with cyclic gamma-globulin combined with ribavirin immediately after admission.…”
Section: Discussioncontrasting
confidence: 72%
“…Preceding the clinical deterioration, significantly enhanced viral load was observed, while the laboratory parameters, especially LDH, AST, CK, PLT, began to deviate sharply from normal ranges [ 49 ]. A previous study [ 37 ] showed that higher numbers of the virus were capable of inducing higher levels of IFN-inducible protein-10 and macrophage inflammatory protein-1 while repressing the production of activation normal T cell expressed and secreted factor, which further cause the severity and even death [ 50 ]. The rapidly rising level of viral load activated the innate and acquired immune system, causing the released of proinflammatory cytokines in quantity, and further aggravating tissues and organs damage [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other cytokine/chemokines were also found to be downregulated, such as tissue polypeptide antigen, platelet-derived growth factor-BB, growth-related oncogene, TGF-β and regulated on activation and normally T-cell expressed (RANTES), compared with those in healthy controls (66,(77)(78)(79). In particular, RANTES was reported to be negatively correlated with viral load (80). However, the expression profile of cytokines in patients with SFTS remain contested.…”
Section: Innate Immunity In Sftsmentioning
confidence: 99%